Functional enhancement of chitosan and nanoparticles in cell culture, tissue engineering, and pharmaceutical applications - Gao, Wenjuan; Lai, James C. K.; Leung, Solomon (Frontiers in Physiology, 2012)
Abstract: As a biomaterial, chitosan has been widely used in tissue engineering, wound healing, drug delivery, and other biomedical applications. It can be formulated in a variety of forms, such as powder, film, sphere, gel and fiber. These features make chitosan an almost ideal biomaterial in cell culture applications, and cell cultures arguably constitute the most practical way to evaluate biocompatibility and biotoxicity. The advantages of cell cultures are that they can be performed under totally controlled environments, allow high throughput functional screening, and are less costly, as compared to other assessment methods. Chitosan can also be modified into multilayer composite by combining with other polymers and moieties to alter the properties of chitosan for particular biomedical applications. This review briefly depicts and discusses applications of chitosan and nanoparticles in cell culture, in particular, the effects of chitosan and nanoparticles on cell adhesion, cell survival, and the underlying molecular mechanisms: both stimulatory and inhibitory influences are discussed. Our aim is to update the current status of how nanoparticles can be utilized to modify the properties of chitosan to advance the art of tissue engineering by using cell cultures.